Design and Build a Fountain Control System Using the Internet Of Things - Tugino; Prasojo, Muklis F. Azari; Prasojo, Joko Prasojo (ReTII, 2020)
The current fountain control system generally still uses direct control in the place where the fountain is installed so that many obstacles are encountered, such as the operator having to monitor and control directly. Internet of Thing (IoT) is a concept where an object has the ability to transfer data over a network without requiring human-to-human or human-to-computer interaction. This research was conducted to create a fountain control system that applies IoT technology which is realized in the form of a fountain prototype and describes the real-time performance of each control using NodeMCU ESP8266 as a controller that communicates via the internet. The results of this research experiment were able to control and monitor the fountain using the Blynk and laptop applications. The media used to connect the Blynk application with fountain hardware via the internet network with wifi.